2015
DOI: 10.1161/hypertensionaha.115.03480
|View full text |Cite
|
Sign up to set email alerts
|

Higher Blood Pressure as a Risk Factor for Diseases Other Than Stroke and Ischemic Heart Disease

Abstract: H ypertension is an established risk factor for stroke, ischemic heart disease, 1,2 and renal dysfunction. 3 The management and prevention of hypertension are important to the prevention of these diseases. Recent evidence has suggested that hypertension also plays a central role in the underlying pathophysiological condition or at prodromal stages before the development of these diseases. Accumulating evidence also indicates that hypertension seems to be linked with common noncardiovascular diseases including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 89 publications
1
38
1
1
Order By: Relevance
“…Persistently elevated blood pressure may lead to stroke, myocardial infarction, congestive heart failure, renal failure and blindness. 1,2 In 2010, 1.3 billion people in the world were suffering from hypertension, with an annual increase rate of 2.5%. 3 According to the World Health Organization (WHO) report published in 2013, the global prevalence of hypertension was 40%.…”
Section: Introductionmentioning
confidence: 99%
“…Persistently elevated blood pressure may lead to stroke, myocardial infarction, congestive heart failure, renal failure and blindness. 1,2 In 2010, 1.3 billion people in the world were suffering from hypertension, with an annual increase rate of 2.5%. 3 According to the World Health Organization (WHO) report published in 2013, the global prevalence of hypertension was 40%.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension, or elevated blood pressure (BP), is a well-recognized risk factor for both cardiovascular and renal diseases in addition to a vast array of diseases contributing significantly to Nutrients 2020, 12, 1163 2 of 17 mortality [8,9]. Specifically, childhood hypertension poses a considerable public health challenge [10], and is associated with essential hypertension in adults and detrimental cardiovascular events [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Two autopsy reports by [12] have shown that hypertension often leads to such sudden and unexplained deaths. Approximately 876 consecutive Ibadan coroners' autopsies show cardiovascular disease as frequent cause of sudden death, and hypertension complications leading to stroke or heart failure [13].…”
Section: Introductionmentioning
confidence: 99%